Pemikiran K.H. Ahmad Dahlan tentang Pendidikan dan Relevansinya dengan Pendidikan Kontemporer - Ushie Uswatun Hasanah; Kurnia Utami Nursholichah; Muh. Asharif Suleman; Anan Marliansyah; Riza Febriansyah (STIKes Ibnu Sina Ajibarang, 2024)
Islamic education in Indonesia faces the challenge of remaining relevant in the modern era while maintaining Islamic values. The thoughts of K.H. Ahmad Dahlan, an early 20th-century Islamic education reformer, offer a potential perspective to answer this challenge. What are K.H. Ahmad Dahlan's main thoughts on education? How are these thoughts relevant to the context of contemporary Islamic education? The purpose of this study is to analyze K.H. Ahmad Dahlan's educational thoughts and evaluate their relevance to contemporary Islamic education to provide insight into the development of Islamic education in the modern era. The research method used a qualitative method with a literature study approach and historical analysis. Data were collected from primary and secondary sources related to K.H. Ahmad Dahlan's thoughts and contemporary Islamic education literature. Research Results: 1. K.H. Ahmad Dahlan's main thoughts include the integration of religious and general knowledge, modernization of teaching methods, inclusive education, practical orientation, character education, and rationality in religion. 2. The thought has significant relevance to contemporary education, especially in the aspects of: a) development of integrated curriculum; b) application of active learning methods; c) emphasis on character education and soft skills; d) rational approach in understanding religion; e) responsiveness to the development of the times. The educational thought of K.H. Ahmad Dahlan is not only relevant but also visionary in the context of contemporary Islamic education. His ideas provide a conceptual framework for the development of a modern and progressive Islamic education system but still adhere to Islamic values. Further adaptation and development of his thought is needed to answer the specific challenges of the digital era and globalization.